The Potential Role of Membrane Technology in the Removal of Microplastics from Wastewater (Journal of Applied Membrane Science & Technology, 2021)
The presence of microplastics in water is a serious environmental problem. Although several approaches have been employed to tackle the problem, the use of membrane technology in addressing this problem remains encouraging but with limitation such as fouling and chemical instability which can be circumvented. This review identifies the presence of microplastics in water and the role of membrane technology in tackling the removal of microplastics in water. The study revealed the presence of microplastics in different water sources as well as the negative impact of microplastics on aquatic animals. Unfortunately, lack of proper management of plastic wastes has led to an increase in the presence of microplastics in the environment. Despite the profound performance by membrane technology towards the removal of microplastics in water, there is need to further improve on the limitations exhibited by this technology. However, there is no doubt that membrane technology remains an outstanding technology for the removal microplastics in water.
Keywords: Microplastics, Membrane bioreactor, Plastics, Ultrafiltration, Wastewater treatment